2019
DOI: 10.15376/biores.14.4.9611-9627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermo-Vibro-Mechanic® Densification Process on the Gloss and Hardness Values of Some Wood Materials

Abstract: This study aimed to determine the gloss and hardness values of low-density wood materials densified using the Thermo-Vibro-Mechanic® (TVM) method after pretreatment with wood stain and wood preservative. This was carried out with a TVM density press that was designed and produced with the support of project 115O138 of the Scientific and Technological Research Council of Turkey (TUBITAK). The samples obtained from Uludağ fir (Abies bornmüelleriana Mattf.) and black poplar (Populus nigra L.) were pretreated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…After mechanical densification, the density of wood can theoretically be increased to a value close to that of the cell wall, approximately 1500 kg/m 3 , and thereby achieve considerable improvements in strength properties (Báder et al 2018). Many previous studies have reported significant increases in the strength properties of mechanically densified wood (Dubey et al 2016;Kariz et al 2017;Pelit et al 2018;Şenol 2018;Song et al 2018;Gao et al 2019). Additionally, the biological resistance of the mechanically densified wood increases depending on the compression ratio (Pelit and Yalçın 2017).…”
Section: Introductionmentioning
confidence: 97%
“…After mechanical densification, the density of wood can theoretically be increased to a value close to that of the cell wall, approximately 1500 kg/m 3 , and thereby achieve considerable improvements in strength properties (Báder et al 2018). Many previous studies have reported significant increases in the strength properties of mechanically densified wood (Dubey et al 2016;Kariz et al 2017;Pelit et al 2018;Şenol 2018;Song et al 2018;Gao et al 2019). Additionally, the biological resistance of the mechanically densified wood increases depending on the compression ratio (Pelit and Yalçın 2017).…”
Section: Introductionmentioning
confidence: 97%
“…Deformations occur in cell wall of compressed wood material under normal atmospheric conditions. In densified wood materials; There are studies in the literature on density analysis and various mechanical properties (Ábrahám et al 2010, Ábrahám and Németh 2012, Arruda and Del Menezzi 2013, Fang et al 2012, Gong et al 2010, Hajihassani et al 2018, Kamke 2006, Kariz et al 2017, Laskowska 2017, Pelit and Sonmez 2015, Rautkari et al 2009, Senol et al 2017, Skyba et al 2009, Ulker et al 2012, Cruz et al 2018, Gao et al 2019, Laskowska 2020, Pertuzzatti et al 2018, determination of changes in surface hardness (Laine et al 2013, Laskowska 2017, Pelit et al 2015b, Rautkari et al 2009, Senol and Budakci 2019, Skyba et al 2009, Ulker et al 2012, microscopic analysis (Blomberg and Persson 2004, Rautkari et al 2010, wettability (Arruda andDel Menezzi 2013, Bekhta andKrystofiak 2016), determination of spring-back amounts (Kariz et al 2017, Pelit and Sonmez 2015, determination of surface properties by applying upper surface processes to surfaces obtained , Pelit et al 2015a, resistance to fungi and termites (Esteves et al 2017, Wehsener et al 2018, color or gloss changes (Ábrahám et al 2010, Cruz et al 2018, Lasko...…”
Section: Introductionmentioning
confidence: 99%
“…As a result of densification, new wood products with high strength properties are developed, and thus low-density species are better utilized (Sandberg et al 2013;Song et al 2018;Fang et al 2019;Laskowska 2020;Sotayo et al 2020;Cabral et al 2022). Densification also improves the surface quality properties of wood such as roughness, contact angle, and gloss Diouf et al 2011;Arruda and Del Menezzi 2013;Büyüksarı 2013;Bekhta et al 2014aBekhta et al , 2017Şenol and Budakçı 2019). Densification is often achieved by compressing the wood in the transverse direction and under suitable heat and/or steam conditions (Seborg et al 1956;Inoue et al 1993a;Navi and Girardet 2000;Kamke and Sizemore 2008;Sandberg et al 2021;Cabral et al 2022).…”
Section: Introductionmentioning
confidence: 99%